Predicting participation in the child care subsidy system from provider features, community characteristics, and use of funding streams. (May 2022) - Slicker, Gerilyn; Hustedt, Jason T.
Highlights: Predictors of provider subsidy participation are examined in a national sample. Centers' funding structures are significant determinants of subsidy participation. Centers in high poverty areas are more likely to participate. Providers that serve infants and toddlers have greater odds of participation. Abstract: Child care is not affordable for many U.S. families, particularly those living in poverty. Child care subsidies and other sources of public funding for early education can assist low-income families with accessing child care. However, the number of providers that accept child care subsidies is declining, threatening both the sustainability of these government programs and access to early care and education for families from low-income backgrounds. The current study identifies factors that may influence center-based child care providers' subsidy system participation using nationally representative data from the 2012 National Survey of Early Care and Education (n = 7771). Our results suggest that certain features of providers, such as having a quality rating, and the poverty density of the community within which a center operates may be positively related to subsidy system participation. In addition, we find that programs serving infants and toddlers are more likely to accept child care subsidies than early childhood programs that focus exclusively on preschool-age children. Findings also indicate that receipt of other sources of public and private funding is associated with subsidy system participation. The findings of this study help identify priorities for policymakers seeking to incentivize provider participation in the subsidy system.